QUANTIFICATION OF 39AR RECOIL EJECTION FROM GA1550 BIOTITE DURING NEUTRON IRRADIATION AS A FUNCTION OF GRAIN DIMENSIONS - Paine J.H.; Nomade S.; Renne P.R. (My University, 2006)
This study presents the first measurement of 39Ar recoil ejection loss from individual, dimensionally characterized mineral grains due to neutron irradiation, and reveals the extent to which this recoil loss is problematic for 40Ar/39Ar dating. Using the well-characterized biotite standard GA1550, known to have between grain reproducibility of 40Ar*/39ArK of order 0.1%, we measured the thicknesses (3-210 μm) and surface areas (0.07-0.90 mm2) of 159 grains selected to span the dimensional range represented in the aliquot. Thinner grains with high surface area/volume (SA/V) reveal elevated 40Ar/39Ar, as much as 26% higher than thicker grains expected to suffer proportionately negligible depletion. Although the thinner grains yield intrinsically less precise measurements due to small 39Ar ion beams, a regular decrease in net recoil loss with increasing biotite grain thickness is clear for grains thinner than ca. 50 μm. Grains thicker than 50 μm reveal essentially no 39Ar loss within analytical uncertainties. The measured 39Ar loss spectrum is significantly higher than predicted by previous modeling approaches. These results suggest a practical threshold of ca. 50 μm grain thickness for biotites, and probably other phyllosilicates,irradiated with 235U fission spectrum neutrons in order to avoid recoil artifacts. Poor agreement between our data and simulation results indicates that recoil displacement models should be revisited in order to resolve the discrepancy. Further empirical work to determine the recoil loss of 39Ar in other minerals is important not only for routine age measurements, but also to shed more light on the role of recoil in multi-diffusion domain theory and other thermochronologic applications exploiting variable diffusion radii and/or grain size effects. © 2005 Elsevier Inc. All rights reserved.